Studium nad intonacją wymowy scenicznej w spektaklach Jerzego Grotowskiego - Gałdyńska-Mazan, Adriana (Investigationes Linguisticae, 2007)
In the present article, an attempt is made to analyse scenic speech intonation in the spectacles by Jerzy Grotowski. The intonational phenomena which are discussed here are interesting for both for linguistics and musicologists. They comprise a part of the phonosphere which includes also other kinds of sound phenomena such as non-articulated sounds, special (rhythmical) walking, jumping or employing theatrical requisites as musical instruments. The melo-rhythmical structure of intonation realized in the theatrical adaptations by Grotowski determines the character of segmental pronounciation, placing it between that typical of speaking and the one present in the singing voice.